Sammlung Thomas : Kunst aus den achtizger Jahren. - Fehlemann, Sabine; Thomas, Raimund (München : A Art 11 Forum Thomas, 1987)
A-One ; Ahearn, John ; Anzinger, Siegfried ; Barceló, Miguel ; Basquiat, Jean-Michel ; Blade ; Bosman, Richard ; Bowes, David ; Brown, James ; Buthe, Michael ; Chia, Sandro ; Christian, Abraham David ; Clemente, Francisco ; Cragg, Tony ; Crash ; Cucchi, Enzo ; Daze ; Disler, Martin ; Fetting, Rainer ; Hacker, Dieter ; Haring, Keith ; Hien, Albert ; Jetelová, Magdalena ; Lamas, Menchu ; Lee ; Leiro, Francisco ; Macdonald, Chris ; etc.
Sammlung Thomas : Kunst aus den achtizger Jahren, A Art 11 Forum Thomas, München, 1987
boek